2008
DOI: 10.1103/physrevlett.101.215002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quasihelical Symmetry on Trapped-Electron Mode Transport in the HSX Stellarator

Abstract: This Letter presents theory-based predictions of anomalous electron thermal transport in the Helically Symmetric eXperiment stellarator, using an axisymmetric trapped-electron mode drift wave model. The model relies on modifications to a tokamak geometry that approximate the quasihelical symmetry in the Helically Symmetric eXperiment (particle trapping and local curvature) and is supported by linear 3D gyrokinetic calculations. Transport simulations predict temperature profiles that agree with experimental pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…15 The regions of bad normal curvature and particle trapping are highly correlated, and previous linear gyrokinetic modeling has indicated that the TEM is highly localized in the bad curvature region of HSX. 16 Combined with temperature or density gradients, there is strong drive for curvature driven modes such as the TEM. 17 Figure 8 shows unstable flux tube samples the region of low magnetic field strength on the inboard side of the device.…”
Section: Comparison To Gyrokinetic Calculationsmentioning
confidence: 99%
“…15 The regions of bad normal curvature and particle trapping are highly correlated, and previous linear gyrokinetic modeling has indicated that the TEM is highly localized in the bad curvature region of HSX. 16 Combined with temperature or density gradients, there is strong drive for curvature driven modes such as the TEM. 17 Figure 8 shows unstable flux tube samples the region of low magnetic field strength on the inboard side of the device.…”
Section: Comparison To Gyrokinetic Calculationsmentioning
confidence: 99%
“…Recently, a modified version of the Weiland ITG/TEM model 6,7 was used to model the anomalous transport in HSX. 28 The results suggest that the anomalous transport in HSX can be explained by TEM transport driven by both electron temperature and density gradients in the helically symmetric geometry. It is natural to question whether the measured turbulence is consistent with this model prediction, or if the transport prediction is simply fortuitous.…”
Section: Introductionmentioning
confidence: 87%
“…It is important to note that while the local electron tem- perature gradient may be relatively small in the edge with the diagnostic probes inserted, a strong density gradient ͑a / L n Ϸ 2-3͒ remains that is capable of destabilizing the TEM, 28 which can drive the resulting turbulence and transport.…”
Section: Experimental Background and Measurement Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) aims at mitigating the neoclassical (nc) losses to the point where anomalous transport becomes dominant over most of the plasma column. Attention is now turning to understanding the effects of 3D geometry on microturbulence, [2][3][4][5][6][7] aided by nonlinear gyrokinetic codes valid for 3D. Supported by the scant, albeit promising, existing findings in this area, we attempt to identify key geometrical factors which contribute to the development and, subsequently, control of turbulent transport levels.…”
mentioning
confidence: 99%